Effect of Preharvest Abiotic Stresses on the Accumulation of Bioactive Compounds in Horticultural Produce - Toscano, Stefania; Trivellini, Alice; Cocetta, Giacomo; Bulgari, Roberta; Francini, Alessandra; Romano, Daniela; Ferrante, Antonio (Frontiers in Plant Science, 2019)
The quality of horticultural products is the result of the interaction of different factors, including grower’s crop management ability, genotype, and environment. Sub-optimal environmental conditions during plant growth can induce abiotic stresses and reduce the crop performance with yield reduction and quality losses. However, abiotic stresses can induce several physiological, biochemical, and molecular responses in plants, aiming to cope the stressful conditions. It is well known that these abiotic stresses are also elicitors of the biosynthesis of many metabolites in plants, including a wide range of bioactive compounds, which firstly serve as functional molecules for crop adaptation, but they have also a great interest for their beneficial effects on human health. Nowadays, the consumer is oriented to low energy foods with low fat content, but at the same time, growing attention is paid to the presence of bioactive molecules which are recognized as health-related compounds and concur to the nutraceutical value of plant-derived foods. In this contest, fruit and vegetables play an important role as source of bioactive ingredients in the diet. At the cultivation level, the understanding of crop responses to abiotic stresses and how they act in the biosynthesis/accumulation of these bioactive compounds are crucial. In fact, controlled abiotic stresses can be used as tools for improving the nutraceutical value of fruit and vegetables. This review focuses on the quality of vegetables and fruits as affected by pre-harvest abiotic stressors, with particular attention to the effect on the nutraceutical aspects.